CFAP70 mutations lead to male infertility due to severe astheno-teratozoospermia. A case report - Beurois, Julie; Martinez, Guillaume; Cazin, Caroline; Kherraf, Zine-Eddine; Amiri-Yekta, Amir; Thierry-Mieg, Nicolas; Bidart, Marie; Petre, Graciane; Satre, Véronique; Brouillet, Sophie; Touré, Aminata; Arnoult, Christophe; et al. (Human reproduction (Oxford), 2019)
Abstract The use of high-throughput sequencing techniques has allowed the identification of numerous mutations in genes responsible for severe astheno-teratozoospermia due to multiple morphological abnormalities of the sperm flagella (MMAF). However, more than half of the analysed cases remain unresolved suggesting that many yet uncharacterised gene defects account for this phenotype. Based on whole-exome sequencing data from a large cohort of 167 MMAF-affected subjects, we identified two unrelated affected individuals carrying a homozygous deleterious mutation in CFAP70, a gene not previously linked to the MMAF phenotype. One patient had a homozygous splice variant c.1723-1G>T, altering a consensus splice acceptor site of CFAP70 exon 16, and one had a likely deleterious missense variant in exon 3 (p.Phe60Ile). The CFAP70 gene encodes a regulator protein of the outer dynein arms (ODA) strongly expressed in the human testis. In the sperm cells from the patient carrying the splice variant, immunofluorescence (IF) experiments confirmed the absence of the protein in the sperm flagellum. Moreover, IF analysis showed the absence of markers for the ODAs and the central pair complex of the axoneme. Interestingly, whereas CFAP70 staining was present in sperm cells from patients with mutations in the three other MMAF-related genes ARMC2, FSIP2 and CFAP43, we observed an absence of staining in sperm cells from patients mutated in the WDR66 gene, suggesting a possible interaction between two different axonemal components. In conclusion, this work provides the first evidence that loss of CFAP70 function causes MMAF and that ODA-related proteins may be crucial for the assembly and/or stability of the flagellum axoneme in addition to its motility.